Manufacture and Characterization of Polymer Concrete with Pumice Aggregates, Banana Stem Fibers, and Styrofoam Waste as Fillers - Nasution, Syaifullah Aldi; Fauzi, Fauzi (Journal of Technomaterial Physics, 2022)
This study aims to determine the effect of replacing some fractions of pumice stone with banana stem fiber in polymer concrete. The ratio of sand, pumice stone, and banana stem fiber were (25:35:0), (25:33:2), (25:31:4), (25:29:6), (25:27:8) in units of weight %. The matrix used was 10% of styrofoam with the addition of 40% epoxy resin. Parameters tested include physical tests (density, porosity, and water absorption), mechanical tests (hardness, flexural strength, and compressive strength), microstructure, and elemental content tests using SEM-EDX. The test results show that the optimum physical properties for density are 1.4 g/cm3, porosity 0.25 %, and water absorption 0.204 %. Meanwhile, the optimum value of mechanical properties in the hardness test is 56.0166 HVN, the flexural strength 26.830 MPa, and the compressive strength 34.082 MPa. Moreover, the morphological and elemental analysis results showed the formed pores, the distribution of the epoxy, and the elements loaded on the polymer concrete samples.